Pelaksanaan Tindak Pidana Pemerkosaan (Studi Komparasi antara Hukum Islam dan Qanun Jinayat di Aceh) - Nurhayati, Nurhayati (Fakultas Syariah IAIN Purwokerto, 2018)
Rape is a sexual crime that indicates highly enough rate in Indonesia. Rape according to the view of Islamic law is different from adultery. Adultery is sexual intercourses between man and woman without legal marriage and carried out consciously on the basis of mutual needs. Rape is not doing of just sexual intercourse but it has additional element that is carried out with force, violence or threats. Sanctions against rapists according to Islamic law is exactly the same as the act of adultery that is stoning and damping. Such sanctions apply only to rapists and not to the victim. Aceh’s Qānūn on Jināyat (criminal) law for the people is regulated in Regional Regulation (PERDA) No. 6 of 2014. Qānūn Jināyat for the people of Aceh is a unity of criminal law formed based on Islamic Shari'ah values ​​derived from the Qur’an and Ḥadīṡ. According to Qānūn Jināyat Aceh, everyone doing sexual rape crime is threatened with ‘uqūbat ta’zīr which in its application there is a difference of punishment with what is in the view of Islamic law.